Meeting the Challenge of Postmodernism: An Integrative Approach to Expository Preaching - Moses, Steven R. (2012)
CIVINS === This thesis will examine the philosophical shift of postmodernity, along with 2 its challenges and opportunities for ministry. I have intentionally limited the scope of this thesis to the epistemological issues relating to postmodernism and their implications for preaching. Where it is relevant, I will raise some of the social and cultural issues relating to postmodernism, but these will be limited in scope. The focus of this thesis is in providing an answer to the question, How do we preach to postmoderns in order to bring about transformation in their lives? In order to investigate this question, we will examine a wide variety of sources which describe this current shift of postmodernism and various approaches that have been advocated for meeting this new challenge. In addition, we will examine the various homiletical methods, both past and present, to determine the best model for connecting with postmodern audiences. In arriving at an answer to the research question, we will argue that the truths of Scripture need not be watered down and though preaching to postmoderns requires some contextualization, it is certainly possible to bridge that cultural gap and face squarely the challenge postmodernism poses for preaching in the 21st Century.